BIOLOGICAL RESISTANCE OF THERMALLY TREATED Corymbia citriodora (Hook.) K.D. Hill & L.A.S. Johnson E Pinus taeda L. WOODS AGAINST XYLOPHAGOUS TERMITES - Juarez Benigno Paes; Pedro Gutemberg de Alcântara Segundinho; Allan Ewerton Rezende Euflosino; Márcio Rogério da Silva; Carlito Calil Junior; André Luis Christoforo (Revista Árvore)
ABSTRACT This research aimed to evaluate the effect of the thermal-treated temperature to improvement of Corymbia citriodora and Pinus taeda wood resistance to the xylophagous termite Nasutitermes corniger, into forced feeding assay. The wood thermally treated was performed at temperatures of 160, 180, 200, 220, 240ºC. For Pinus taeda, the temperature of 260ºC was also used. Three boards of 6 × 16 × 56 cm (thickness × width x length) were used for each temperature. After being thermally treated, the boards were transformed into samples of 2.54 × 2.54 × 0.64 cm (longitudinal × radial × tangential). The experiment was kept in a climatized room (25 ± 2ºC and 65 ± 5% of relative humidity), for 28 days. For Corymbia citriodora, the thermal treatment at 220 and 240ºC improved the resistance to the termite. For Pinus taeda, the resistance improvement occurred at 240 and 260ºC. The temperature of 160ºC caused a decrease in the natural durability of both species.